Clinical Correlation of Reflux Finding Score with Reflux Symptom Index in Diagnosis & Management of Laryngopharyngeal Reflex Disease in A Tertiary Care Hospital, Western Up - Gaur, Sushil; S Panakkal, Akshay; Arora, Udita; Singh, Vandana (ENT Updates, 2021)
Objective: The retrograde flow of gastric contents to the upper aerodigestive tract is known as laryngopharyngeal reflux disease (LPRD). It is also known as extraesophageal reflux disease and is a common condition seen in otolaryngology practice. Diagnosis of LPRD is difficult as the patients present with vague and indistinct symptoms. Reflux symptom index (RSI) is a 9-item questionnaire for evaluating symptoms of LPR, whereas the reflux finding score (RFS) is an 8-item clinical severity scale used to interpret the most common larynxgoscopic findings related to LPR. In this study, we aimed to correlate RSI with RFS in symptomatic patients to investigate the reliability of RSI in the diagnosis of LPRD. Methods: In this study, we included100 patients attending the Otorhinolaryngology OPD at Santosh Hospital, Ghaziabad, India, with symptoms suggestive of reflux disease. The patients were asked to fill the RSI scoresheet in the first stage and patients with RSI >13 were chosen for the study. A total of 81 patients were chosen and examined by video-assisted 70° direct laryngoscopy to determine the RFS. The correlation between RSI and RFS were investigated. Result: The study group included 81 patients presented with various symptoms of LPR. Upon investigating further with RFS and RSI we observed that only 7 patients of 81 had a positive score on RSI with a negative score on RFS. Conclusion: According to the results of our study, RSI scoring alone is a fast and reliable method for the evaluation and diagnosis of LPR. Our study shows a high correlation between RSI scoring and RFS.